شعرية العتبات النصية في رواية "تاء الخجل" لفضيلة الفاروق - إيمان, ترجات; مسعودة, لعريط (جامعة الوادي - University of Eloued, 2023)
يهدف هذا البحث لقراءة الخطاب الروائي ضمن سلسلة الإحالات النصية المحيطة التي وظفتها الروائية فضيلة الفاروق في رواية "تاء الخجل"، والتي يسعى القارئ إلى إدراكها والكشف على العلائق النصية التفاعلية بين المتن والعتبة من جهة وتعالق العتبات مع بعضها البعض من جهة أخرى. This research aims to read the narrative discourse within a series of surrounding textual references employed by the novelist Fadhila Al-farouk in the novel "Taa Alkhjal", which the reader seeks to understand and reveal the interactive textual relationships between the text and the threshold on the one hand, and the relation of the thresholds between them on the other hand.
Keywords: شعرية العتبات ; الغلاف ; العنوان ; العناوين الداخلية; poetic thresholds ; cover ; title ; subtitles